2004
DOI: 10.4049/jimmunol.172.3.1531
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ Regulatory T Cells Generated Ex Vivo with IL-2 and TGF-β Suppress a Stimulatory Graft-versus-Host Disease with a Lupus-Like Syndrome

Abstract: Regulatory T cells generated ex vivo from conventional mouse T cells have been used to prevent and alter the course of a stimulatory graft-vs-host disease with a lupus-like syndrome. DBA/2 mouse T cells induce this syndrome when injected into (DBA/2 × C57BL/6) F1 mice. Stimulating DBA/2 T cells with irradiated C57BL/6 in the presence of IL-2 and TGF-β induced both CD4+ and CD8+ cells to develop potent suppressive activity and enhanced their survival. The IL-2 and TGF-β-treated T cells lost their ability to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
165
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 42 publications
(29 reference statements)
4
165
2
2
Order By: Relevance
“…Introduction of Treg cell-depleted parental cells induced significantly lower levels of anti-DNA IgG1 in the recipient than did introduction of total parental cells (Figure 1). This result was surprising, because alloantigen-specific Treg cells have been shown to be able to inhibit cGVHD (Zheng et al, 2004;Kim et al, 2005). In these cases, it is thought that a large number of Treg cells can inhibit the activity of alloantigen-specific CD4 + T cells that are prerequisite for breaking self-tolerance of B cells.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Introduction of Treg cell-depleted parental cells induced significantly lower levels of anti-DNA IgG1 in the recipient than did introduction of total parental cells (Figure 1). This result was surprising, because alloantigen-specific Treg cells have been shown to be able to inhibit cGVHD (Zheng et al, 2004;Kim et al, 2005). In these cases, it is thought that a large number of Treg cells can inhibit the activity of alloantigen-specific CD4 + T cells that are prerequisite for breaking self-tolerance of B cells.…”
Section: Resultsmentioning
confidence: 75%
“…Even though it is well known that Treg cells can prevent both aGVHD (Hoffman et al, 2002;Taylor et al, 2002;Edinger et al, 2003) and cGVHD (Zheng et al, 2004;Kim et al, 2005), little is known regarding their involvement in the pathogenesis of cGVHD versus aGVHD. In human cGVHD, there is evidence showing that Treg cells are positively associated with cGVHD (Clark et al, 2004), although contradictory data have been reported more recently (Miura et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treg cells can indeed be expanded ex vivo with allogeneic B cells [70] and these express very high levels of FoxP3, maintain an anergic phenotype, and are potent suppressors capable of inhibiting activated T cell responses [70]. Several previous studies have indeed demonstrated that the adoptive transfer of iTregs can suppress disease development in a lupus syndrome-like model [72,73], experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis [74], an autoimmune gastritis model [75][76], spontaneous development of type 1 diabetes in mice [77], Th1-mediated colitis [78], Th17-mediated diseases [79], and house dust mite-induced allergic pathogenesis in an asthmatic mouse model [80].…”
Section: Adoptive Transfer Therapy Using Regulatory T Cellsmentioning
confidence: 99%
“…In addition to the different CD4 + Treg that have been described, there are reports suggesting that the CD8 + T cell compartment also contains cells with regulatory properties [15][16][17][18][19][20][21]. A report in the present issue of the European Journal of Immunology by Maile et al [22] describes the identification of CD8 + Treg that arise after stimulation with peptide-loaded MHC class I tetramers in vivo.…”
mentioning
confidence: 99%